Characterization of Factor VIII B-Cell Inhibitory Epitopes - Lollar, Pete (Thrombosis and Haemostasis, 1999)
Factor VIII contains three epitopes that are the usual targets of clinically significant antibody inhibitors. Two of these epitopes are located in the A2 and C2 domains of factor VIII. The third epitope appears to be in the A3 domain. Ongoing studies continue to provide higher resolution maps of these epitopes and to understand the mechanism by which inhibitors produce a bleeding diathesis. The manipulation of inhibitor epitopes using recombinant DNA technology may lead to improved forms of factor VIII that have lower antigenicity and/or lower immunogenicity.